Effect of Seaweed Powder on Rheological Properties of Dough and Quality of Germinated Brown Rice Bread - My Duyen Nguyen Dang; Thanh Tung Pham (Journal of Technical Education Science, 2025)
This study investigated the effect of seaweed powder on the rheological properties of dough and the quality of germinated brown rice bread. Germinated brown rice flour was replaced with seaweed powder at levels of 10%, 20%, 30%, and 40% (w/w). Rheological properties of the dough, including viscoelasticity, deformation resistance, and deformation recovery, were evaluated. The effects of seaweed powder on bread quality attributes, such as loaf volume, specific volume, texture, and sensory characteristics, were also determined. The results showed that seaweed powder significantly affected the rheological properties of the dough and the quality of the bread. Dough moisture content decreased, while viscosity and elasticity increased with increasing levels of seaweed powder. The storage modulus (G’) was higher than the loss modulus (G"), indicating a predominantly elastic behavior. Deformation resistance and recovery also increased with increasing seaweed powder substitution. Furthermore, increasing seaweed powder substitution led to a decrease in specific volume and an increase in crumb firmness, chewiness, and resilience. Crumb cohesiveness and springiness decreased with increasing seaweed powder content. Sensory evaluation revealed that bread with 20% seaweed powder substitution was the most preferred. This study suggests that supplementing germinated brown rice bread with 20% seaweed powder can improve its nutritional value while maintaining acceptable sensory qualities.